Analisis Finansial Usaha Budidaya Ikan Nila Desa Merangin Kecamatan Kuok Kabupaten Kampar Provinsi Riau (Studi Kasus: Keramba Yani) - Syahnaz Arsyah Tina Pratiwi; Darwis; Ridar Hendri (JURNAL SOSIAL EKONOMI PESISIR, 2021)
This research was conducted on june 2, 2020 – july 8, 2020 which is located in the Merangin village Kuok sub district Kampar districts Riau province. This study aims to calculate the amount of investment in the cultivation of fish tilapia (oreochromis niloticus) floating net cages in the Merangin village river, to calculate how much revenue and profits in the cultivation business in floating net cages in the merangin village river, and to analyze the feasibility of aquaculture businesses in floating net cages in merangin village. The method used in this research is the case study method with the number of respondents as much as 1 person. Tilapia fish farming business is located in Merangin Village, Kuok Subdistrict, Kampar district, established in 2004 with 11 floating net cages located on the river bank under the first bridge of the Koto Panjang Hydroelectric Power Plant and developing each year, this development can be seen from the total investment spent on the fish farming business. Fish Tilapia in Merangin Village, Kuok Subdistrict, Kampar districts, amounting to Rp. 258.904.000, the components that affect investment are fixed capital and working capital components, namely making floating net cages, water installations, purchasing scales, buckets, buckets, nets, purchasing seeds, purchasing pellet feed, generator set, and drum purchase. Receipt from the fish tilapia farming business is Rp.356.400.000 every year, while the profit earned is Rp. 97.496.000 annually, and the fish tilapia farming business in Merangin Village, Kuok District, Kampar districts is feasible based on a Return Cost Ratio (RCR) of 1.37, Financial Rate of Return (FRR) value of 25.32% and Payback Period of Capital (PPC) 3.9 periods.